Analisis Variabilitas Genetik Rigidoporus microporus (Jamur Akar Putih) pada Karet dengan Teknik PCR-RFLP Fragment ITS - Ria Novianti; Haryono Semangun; Ferry F. Karwur; Martanto Martosupono (Universitas Gadjah Mada, 2011)
The eleven isolates studied fell into two groups, which showed that the fungus did not have high genetic variability. Isolates from diseased rubber trees in shorter vicinities, which were due to pathogen’s vegetative spread through root contact, have close genetic relationship. Meanwhile isolates from far apart trees, either in one estate or from different islands, does not necessarily have distant genetic relationship. It might be due to the fact that long distance dispersal of the disease could also due to rhizomorph contaminating rubber stumps. PCR-RFLP Fragment ITS Techniques can be applied to study genetic relationship of Rigidoporus microporus isolates. It is expected that the technique will be applied with more isolates from different provinces by using additional different restriction enzymes.